A Comparative Study of The Syafiian Mazhab & The Maliki Mazhab from Islamic Law Perspective Regarding The Return of Property as A Result of A Canceled Marriage - Siswanto, Moh. Aris; Hafidz, Jawade (Universitas Islam Sultan Agung, 2025)
A comparative study of four schools of jurisprudence is urgently needed to overcome legal uncertainty in Indonesia regarding the return of inherited assets if the marriage is annulled. The increasing number of marriage annulments in 2024, coupled with differences in interpretations of schools of thought and positive law, makes this study crucial for creating legal certainty, justice and harmonization between Islamic law and positive law in Indonesia. This study will recommend practical solutions to avoid conflict and protect the rights involved. This research uses a normative method with a literature study approach to analyze Islamic law regarding the return of inherited assets when a marriage is annulled. Comprehensive law for fair dispute resolution and the results of the discussion are that the Shafi'i and Maliki schools have different opinions regarding the withdrawal of offerings before the wedding. Shafi'i takes into consideration the giver's intentions, allowing withdrawal if it is for marriage and annulled, despite internal differences of opinion. Malikis are stricter, generally prohibiting withdrawals except from father to son, with the potential exception of pre-covenant dowries. These differences, plus internal differences of opinion within the two schools, demonstrate the complexity of this issue. Implementation in Indonesia faces challenges: differences in sectarian interpretations, difficulty proving intent, gender inequality, and a lack of a modern legal framework. Comprehensive legal reform, increasing legal awareness, and harmonization of Islamic-positive law are very necessary to create justice.